STUDI KASUS WARGA MULTIKULTURAL YOGYAKARTA DI ERA DIGITAL DAN PERAN PENDIDIKAN AGAMA ISLAM - Suryana, Angga (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
The rapid growth of digitalization presents both challenges and opportunities for multicultural societies in maintaining social harmony. Yogyakarta, renowned for its cultural and religious diversity, continues to uphold its identity as an inclusive and tolerant city. This study aims to examine how Yogyakarta’s multicultural communities preserve values of tolerance amid the complexities of the digital era. Utilizing a descriptive qualitative approach, the findings reveal that the city’s tolerant social character is shaped by deeply rooted local cultural values, the strengthening of multicultural education, and the strategic role of Islamic religious education in fostering mutual respect for differences. Furthermore, strong digital literacy plays a crucial role in mitigating misinformation and facilitating constructive dialogue in online spaces. Collaboration among educators, religious leaders, families, and government policy further reinforces the community’s social resilience. These findings underscore that sustaining tolerance in the digital era requires the integration of local wisdom, contextualized education, and wise use of technology. Hence, cross-sectoral synergy emerges as a key strategy in building sustainable social cohesion amid pluralism and societal transformation